2017
DOI: 10.1016/j.cub.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Expression of the Mitotic Activator Cdc25 Suggests a Mechanism of Size Control in Fission Yeast

Abstract: Summary Proper cell size is essential for cellular function. Nonetheless, despite more than 100 years of work on the subject, the mechanisms that maintain cell size homeostasis are largely mysterious [1]. Cells in growing populations maintain cell size within a narrow range by coordinating growth and division. Bacterial and eukaryotic cells both demonstrate homeostatic size control, which maintains population-level variation in cell size within a certain range, and returns the population average to that range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 52 publications
7
102
0
Order By: Relevance
“…As cells grow, Cdc25 levels will increase until they reach the size threshold required to dephosphorylate Cdk1, at which point they will enter mitosis. Consistent with this model, my lab and others have shown that, in fission yeast, Cdc25 accumulates in a size‐dependent manner in G2 . The conservation of Cdc25 across fungi and metazoa allows the possibility that Cdc25 accumulation could be a conserved mechanism of cell‐size control.…”
Section: Potential Candidates For Unstable Activatorsmentioning
confidence: 59%
See 4 more Smart Citations
“…As cells grow, Cdc25 levels will increase until they reach the size threshold required to dephosphorylate Cdk1, at which point they will enter mitosis. Consistent with this model, my lab and others have shown that, in fission yeast, Cdc25 accumulates in a size‐dependent manner in G2 . The conservation of Cdc25 across fungi and metazoa allows the possibility that Cdc25 accumulation could be a conserved mechanism of cell‐size control.…”
Section: Potential Candidates For Unstable Activatorsmentioning
confidence: 59%
“…Thus, accumulating activator models often propose unstable accumulating activators . Accumulating activators have been proposed to regulate entry into mitosis in a variety of unicellular eukaryotes, including Tetrahymena , Amoeba , and fission yeast …”
Section: An Unstable Accumulating Activator Can Regulate Cell Sizementioning
confidence: 99%
See 3 more Smart Citations